Oncogenic roles of serine–threonine kinase receptor-associated protein (STRAP) in osteosarcoma - Dumnoensun Pruksakorn (2018)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature. Purpose: To validate the presence of serine–threonine kinase receptor-associated Protein (STRAP) in osteosarcoma tissue and to investigate the oncological role of STRAP in osteosarcoma. Methods: Expression of STRAP protein in osteosarcoma tissue compared to soft callus (hyperactive bone healing tissue) and in multiple cell lines was examined using western blot analysis. Effects of STRAP silencing on cell proliferation, invasion, migration and re-implantability in chick chorioallantoic membrane (CAM) were observed in osteosarcoma cell lines (MNNG-HOS, 143B, and U2OS). Results: The result demonstrated that STRAP was highly up-regulated in osteosarcoma tissues compared with the normal physiological bone healing tissue (soft callus). Expression level of STRAP was markedly high in osteosarcoma cell lines with aggressive phenotype. Upon STRAP silencing, invasion and migration, but not proliferative activity, were selectively modulated in high-expression-STRAP cell lines. In addition, STRAP silencing reduced the success rate of tumor implantation and growth of MNNG-HOS cells in CAM model. Conclusions: Serine–threonine kinase receptor-associated protein is up-regulated during osteosarcoma progression. The presence of STRAP enhances osteosarcoma cell invasion, migration and re-implantation ability, factors which play a critical role in metastasis. Serine–threonine kinase receptor-associated protein and its related pathway are worthy for further exploration as a novel target for anti-metastasis agents.